Financial guards at Europol. Participation of the National Tax and Customs Administration and its predecessor, the Hungarian Customs and Finance Guard in the workof the European Union Agencyfor Law Enforcement Cooperation - Kristóf Péter Bakai; Zsolt Csatlós (Belügyi Szemle)
Aim: To give an overview of the cooperation between Europol and the National Tax and Customs Administration.